Une petite histoire de l'alimentation française - Bellemain, Véronique (éditions Quae, 2017)
To mark its 30th anniversary, the National Food Council interviewed the players who have contributed to its history. Some opted to write a reflective account of their experience. Others produced a theoretical assessment of their disciplines. These different angles of approach identify what makes heritage and the contribution of the National Food Council to the public food policies and actions. You can download the ePub either consult the directly on-line interactive frieze.